Early Signs of Pathological Cognitive Aging in Mice Lacking High-Affinity Nicotinic Receptors - Konsolaki, Eleni; Tsakanikas, Panagiotis; Polissidis, Alexia V.; Stamatakis, Antonios; Skaliora, Irini (Frontiers in Aging Neuroscience, 2016)
In order to address pathological cognitive decline effectively, it is critical to adopt early preventive measures in individuals considered at risk. It is therefore essential to develop approaches that identify such individuals before the onset of irreversible dementia. A deficient cholinergic system has been consistently implicated as one of the main factors associated with a heightened vulnerability to the aging process. In the present study we used mice lacking high affinity nicotinic receptors (β2-/-), which have been proposed as an animal model of accelerated/premature cognitive aging. Our aim was to identify behavioral signs that could serve as indicators or predictors of impending cognitive decline. We used test batteries in order to assess cognitive functions and additional tasks to investigate spontaneous behaviors, such as species-specific activities and exploration/locomotion in a novel environment. Our data confirm the hypothesis that β2-/- animals exhibit age-related cognitive impairments in spatial learning. In addition, they document age-related deficits in other areas, such as recognition memory, burrowing and nesting building, thereby extending the validity of this animal model for the study of pathological aging. Finally, our data reveal deficits in spontaneous behavior and habituation processes that precede the onset of cognitive decline and could therefore be useful as a non-invasive behavioral screen for identifying animals at risk. To our knowledge, this is the first study to perform an extensive behavioral assessment of an animal model of premature cognitive aging, and our results suggest that β2-nAChR dependent cognitive deterioration progressively evolves from initial subtle behavioral changes to global dementia due to the combined effect of the neuropathology and aging.